La forêt linéaire - Denis Delbaere (Projets de Paysage)
The problems posed in the management of the wooded coppices which form, due to a lack of maintenance, on the slopes of the embankments and in the planted areas along major transport infrastructures offer an opportunity to study the case of a landscape project in the Likoto Eurometropolis (Lille Kortrijk Tournai). The team in charge of managing the local transport infrastructures follow an approach based on the containment of this linear forest which has been allowed to develop freely at a distance from motorways, railway tracks and station platforms. Such approaches allowing vegetation to grow freely also encourage the social practices of temporary dwellings and leisure activities that take advantage of the "forest" cover. At the same time, in recent years has emerged a more reasoned approach to the afforestation of infrastructures as a resource for the aesthetic and economic development of these areas through the production and exploitation of the biomass. In recent years, even the authorities in charge of the maintenance of these transport infrastructures have come to see these forms of afforestation as a resource rather than a constraint. Such a change in the perception of this potential forest may be considered as the heritage of long-standing landscape projects such as the Belgian Green Plan of 1958 or the Nord-Pas-de-Calais regional forest and the "new forestry model" the latter has come to represent. The plasticity of the forest model, motivated by theoretical debates on landscape ecology (notably the island theory and the SLOSS), seen from this perspective, would imply a re-appropriation of these wooded wastelands in the form of a linear forest on the edges of transport infrastructures.